Óleo essencial de Zingiber officinale na dieta de carpa-capim (Ctenopharyngodon idella): parâmetros metabólicos e desempenho zootécnico - Brasil, Marisa Teresinha de Bastos (2019)
Fish farming has been showing productive growth of extreme significance within aquaculture production, a fact that has been causing an increase in fish production with a consequent increase in density in nurseries. A negative of this trend of production are the economic losses due to diseases that high stocking rates can stimulate, bringing to the producer the need to establish more effective management techniques, nutritionally safer foods, and adopt more efficient prophylactic methods. The prophylactic use of natural products has aroused interest in this sector, since they have lower possibilities of toxicity to animals and high biodegradable potential. The objective of this study was to evaluate the effect of the addition of OE from Zingiber officinale (EOG) on juvenile rations of carp-grass, and its relation on growth and metabolic parameters in fish plasma and tissues. 500 juvenile carp (2.5 ± 0.54 g) were distributed in 20 boxes of 30 liters each, in a recirculation system, where they received commercial feed (40% CP) supplemented with EOG at concentrations of 0; 0.25; 0.5; 1.0 and 2.0 mL/kg-1 of feed. The water quality parameters were monitored and adjusted when necessary, and remained within acceptable levels for fish. Liver, muscle and plasma samples were collected as well as measurements of fish weight and length for subsequent growth analysis, centesimal composition of the whole fish and metabolic parameters of the animals. It was observed that none of the OEG levels added to the feed had a positive effect on the growth of carp fingerlings. The concentration of 2.0 mL of OEG / kg-1 of feed can be used for tests on carnivorous or omnivorous species, since these have a lower digestive tract and possibly the recovery and absorption will be promising.